How the Universe and Living Beings Are Created and How Human Could Be Liberated and Merged into Cosmic Consciousness - Mahesh Man Shrestha (Studies in Social Science & Humanities, 2024)
Cosmic energy and cosmic consciousness is the key to form universe and living beings in the cosmos. The process of death and rebirth will continue until “nirvana or liberation” is attained. “Karma” is the works accomplished by us with the “cause and effect” principle. “Bhakti” means the complete devotion towards the Supreme. “Bhakti” should not be performed on a ritual basis but performed with the devotion then only one could achieve the “Nirvana”. All the good and bad works done by us are stored in our consciousness which fixes the direction of our next life. Quantum mechanics has compelled us to accept unintelligible mechanism of natural phenomenon-like the jump of the electron-and we do not hesitate to accept them likewise with the data and observations available we are compelled to accept the rebirth.